Demographic Patterns and Clinical Distribution of Refractive Errors in Patients Attending a Tertiary Eye Care Center - Fayaz Ahmed Soomro, Abdul Qadeem Soomro, Abdul Sattar, Asif Qazi, Shoaib Ahmed Shaikh, Abdullah Laghari, Anas Bin Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Refractive errors are a leading cause of avoidable visual impairment worldwide. Despite being easily correctable, uncorrected refractive errors remain prevalent, particularly in low-resource settings, affecting quality of life and productivity. Objective: To determine the pattern of refractive errors among patients attending a tertiary eye hospital and assess associations with age, gender, and occupational status. Methods: A hospital-based cross-sectional study was conducted involving 1,749 patients aged ≥5 years. Visual acuity was assessed using the Snellen chart, followed by objective and subjective refraction; cycloplegic refraction was performed when indicated. Refractive errors were classified into myopia, hypermetropia, astigmatism (and subtypes), presbyopia, and amblyopia. Demographic data including age, gender, and occupation were recorded. Data were analyzed using descriptive statistics and chi-square tests, with p<0.05 considered significant. Results: Females exhibited higher frequencies of hypermetropia, astigmatism, and simple variants of myopic and hyperopic astigmatism. Myopia was most common in individuals aged 16–40 years, while hypermetropia and presbyopia increased with age. Occupational analysis revealed a higher burden of myopia, hypermetropia, and astigmatic subtypes among unemployed participants, whereas presbyopia was more frequent in employed individuals. These trends suggest that refractive errors are influenced by physiological aging, lifestyle, occupational visual demands, and healthcare-seeking behaviors. Conclusion: Refractive errors are prevalent across all age groups, with distinct patterns linked to gender, age, and occupation. Early detection, regular screening, and accessible refractive services are essential to reduce avoidable visual impairment and improve quality of life, particularly in underserved populations. Keywords: Refractive Errors, Myopia, Hypermetropia, Astigmatism, Tertiary Eye Care